Effect of the Deposition Temperature on the Device Performance of the Nanostructured ZnO Thin Film Transistor by Sol Gel Method - Ruzgar, Serif; Ozkan, Aziz Ertugrul; Caglar, Mujdat; Aksoy, Seval; Ilican, Saliha; Caglar, Yasemin; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2014)
In this study, the nanostructured ZnO thin film transistors (TFTs) were fabricated by using sol-gel spin-coating method and the deposition temperature effect on the structural and morphological properties of active layer ZnO TFTs were investigated. The crystallinity of active layer was improved with deposition temperature. An increase in the crystallite size depending on the increase in deposition temperature was observed in both scanning electron microscopy (SEM) micrographs and X-ray diffraction (XRD) results. The prepared TFTs exhibited the n-channel behavior due to the n-type electrical conductivity of the ZnO active layer. The saturation mobility that is one of the important parameters of transistor was significantly affected by the deposition temperature and reached 5.28 cm(2)V(-1)s(-1) at 750 degrees C.
Keywords: ZnO; Sol-Gel Spin Coating Method; Thin Film Transistor